FUNCTIONAL PROPERTIES OF ENZYMETICALLY MODIFIED WHEAT GLUTEN - & Nasser, Jasim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to investigate the potentiality of gluten inclusion into functional foods. The effect of controlled enzymatic hydrolysis on the antioxidant properties of Pepsin, Trypsin, and Papain-assisted wheat gluten hydrolysates have been studied. Lyophilized and dried gluten from durum wheat, commercial durum gluten, and whey proteins were enzymatically hydrolyzed. Based on the antioxidant activity of the obtained hydrolysates, papain hydrolyzed gluten was selected for this study. Functional properties (water holding capacity, emulsifying capacity and stability, foam formation and stability, protein solubility, and oil binding capacity) were investigated for the selected samples. Results revealed that the enzymatic modification improved the functional properties of  all  selected proteins significantly (P